2008
DOI: 10.1021/nn8004069
|View full text |Cite
|
Sign up to set email alerts
|

Half-Metallic Zigzag Carbon Nanotube Dots

Abstract: A comprehensive first-principles theoretical study of the electronic properties and half-metallic nature of finite zigzag carbon nanotubes is presented. Unlike previous reports, we find that all nanotubes studied present a spin-polarized ground state, where opposite spins are localized at the two zigzag edges in a long-range antifferomagnetic configuration. Relative stability analysis of the different spin states indicate that, for the shorter segments, spin-ordering should be present even at room temperature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 95 publications
(332 reference statements)
6
72
2
Order By: Relevance
“…This state also has a frustrated AFM distribution of spins. Hod and Scuseria 14 have shown that δ(μ 0 T ) decreases sharply for long finite ZNTs, becoming lower than the thermal energy at room temperature (0.025 eV) in most cases. One of the aims of this work is to analyze the changes induced in the magnetic state of the nanotubes by the presence of an encapsulated iron cluster; we discuss this topic in the next section.…”
Section: B Finite Zigzag Carbon Nanotubesmentioning
confidence: 91%
See 2 more Smart Citations
“…This state also has a frustrated AFM distribution of spins. Hod and Scuseria 14 have shown that δ(μ 0 T ) decreases sharply for long finite ZNTs, becoming lower than the thermal energy at room temperature (0.025 eV) in most cases. One of the aims of this work is to analyze the changes induced in the magnetic state of the nanotubes by the presence of an encapsulated iron cluster; we discuss this topic in the next section.…”
Section: B Finite Zigzag Carbon Nanotubesmentioning
confidence: 91%
“…The energy difference E(μ 0 T ) − E(AFM) between the lowest-lying magnetic state (with total magnetic moment μ 0 T ) and the ground state (AFM) decreases monotonically when the length of the nanotube increases, up to a point where the difference becomes lower than room temperature. 14 For the shortest zigzag carbon nanotubes, E(μ 0 T ) − E(AFM) increases when the diameter of the nanotube increases, showing an oscillating effect. 16 Our aim is to analyze the interplay between the singular magnetic properties of the finite ZNTs and the large magnetization of the encapsulated Fe clusters.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…49 (8, 16 )] to check the effect of the carbon circles on the electronic structure of the nanotube. The HOMO−LUMO energy gap of (8,0) BCNNT e is 1.00 eV, and the dipole moment is 20.2 D. The net charge on carbon atoms in BCNNTs is relatively small, and the carbon circles serve as a bridge for π conjugation, as revealed by the charge distribution of these nanotube clips ( Figure S1).…”
Section: ■ Models and Computational Detailsmentioning
confidence: 99%
“…The model consists of a zigzag, fixed-fixed, single-wall CNT. Zigzag refers to the chirality of the CNT, which is (n, m) ¼ (10, 0) [53]. The length L of the CNT is 52.62 Å and the CNT diameter D equals 7.83 Å.…”
Section: Defect Free Cnt Bucklingmentioning
confidence: 99%